KEMAMPUAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 2 TELUK KUANTAN - Tania Kasanty Guntari; Hermandra Hermandra; Abdul Razak (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Absrtact: This research aimed to describe the level of ability to write descriptive text of class VII Teluk Kuantan 2 junior high school students, and describes the comparison of the writing descriptive text between male and female students of class VII Teluk Kuantan 2 Junior High School. Writing descriptive text is the ability of writing descriptive text in providing title, general description, part description, conclusion by using chosen topic. The method used in this research is quantitative descriptive method. The data source used was the score of the ability to write descriptive text of class VII students of SMPN 2 Teluk Kuantan. The test was conducted by using a test the normality of a single data curve, ad using the independent samples T test. Based on the test results, it was concluded that the ability to write descriptive text of class VII student of SMPN 2 Teluk Kuantan was classified as moderate and there was no difference in the ability to write descriptive text between male and female students of class VII students of SMPN 2 Teluk Kuantan.Key Words: descriptive text, writing skill